2011
DOI: 10.1186/2045-824x-3-20
|View full text |Cite
|
Sign up to set email alerts
|

Dll4-Notch signaling as a therapeutic target in tumor angiogenesis

Abstract: Tumor angiogenesis is an important target for cancer therapy, with most current therapies designed to block the VEGF signaling pathway. However, clinical resistance to anti-VEGF therapy highlights the need for targeting additional tumor angiogenesis signaling pathways. The endothelial Notch ligand Dll4 (delta-like 4) has recently emerged as a critical regulator of tumor angiogenesis and thus as a promising new therapeutic anti-angiogenesis target. Blockade of Dll4-Notch signaling in tumors results in excessive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 76 publications
4
79
1
Order By: Relevance
“…5D). Expression of Dll4 was strongly repressed, in agreement with the observed increased vascular density and hypoxia, but in apparent contradiction with the enhanced tumor development (24). Of note, flt-1 expression was strongly increased in 4T1-Egfl7 tumor endothelial cells, and the expression levels of CD31/PECAM, P-selectin, VE-cadherin, eNOS, and of the integrin subunits av, a3, b1, and b3 were not modified (not shown).…”
Section: Egfl7 Represses Leukocyte Adhesion Molecules In Tumor Endothsupporting
confidence: 53%
“…5D). Expression of Dll4 was strongly repressed, in agreement with the observed increased vascular density and hypoxia, but in apparent contradiction with the enhanced tumor development (24). Of note, flt-1 expression was strongly increased in 4T1-Egfl7 tumor endothelial cells, and the expression levels of CD31/PECAM, P-selectin, VE-cadherin, eNOS, and of the integrin subunits av, a3, b1, and b3 were not modified (not shown).…”
Section: Egfl7 Represses Leukocyte Adhesion Molecules In Tumor Endothsupporting
confidence: 53%
“…S3). This is consistent with an antiangiogenic mechanism of inhibition, and is similar to what has been observed when DLL4 and VEGF inhibitors are combined (28), further suggesting that inhibition of the Notch1 and VEGF pathways is not redundant (23,24,45). Use of a Notch1 antibody may have the added advantage of simultaneously blocking oncogenic activation of Notch1 signaling not only through DLL4 in the stroma, but also through other ligands such as Jag1 or Jag2 in the tumor itself, possibly affecting prosurvival signals in addition to angiogenesis.…”
Section: Discussionsupporting
confidence: 71%
“…It has previously been demonstrated that inhibition of the Notch pathway through blockade of DLL4 can negatively affect tumor growth in preclinical models that are resistant to anti-VEGF therapy (23,24,26,28,45). To see if specific inhibition of the Notch1 receptor can achieve similar results, we used the highly vascular HT-1080 xenograft model, which has been widely used to study tumor angiogenesis.…”
Section: Treatment With 23814 Alters Tumor Vasculature and Inhibits Tmentioning
confidence: 99%
“…Due to the role of vascular endothelial growth factor (VEGF) and fibroblast growth factor (FGF), endothelial cells greatly proliferate (24)(25)(26). Meanwhile, tube-like structure formation and vascular function are achieved by delta like canonical Notch ligand 4 (Dll4)/Notch-1 signaling (27)(28)(29)(30). Tumor angiogenesis is a complex process that includes multiple stages and is regulated by numerous signaling molecules that interact with one another (18).…”
Section: Introductionmentioning
confidence: 99%